Evaluation Of The Algerian Experience In Implementing The Local Production System - Derbal ,Soumeia (جامعة الوادي University of Eloued, 2025)
This research paper aims to address the issue of implementing the Local Production System (LPS) program in Algeria and its role in developing the traditional industry and crafts sector. The program is a cornerstone for executing the developmental plan to advance this sector. Answering the research question required using an analytical method to assess the effectiveness of the program's implementation on the ground. The analysis confirmed the program's success in developing Algeria's the traditional industry and crafts sector. This was fulfilled by facilitating the role of responsible bodies in organizing and supervising joint projects among craftsmen, building trust, and fostering cooperation among several actors within each local production system. Additionally, the program enabled craftsmen to secure projects and achieve local accomplishments. Expanding the implementation of this program across different sector activities and throughout all provinces would help ensure sustainable development for the traditional industry and crafts sector.
Evaluation of the Algerian Experience in Implementing the Local Production System (LPS) Program in the Traditional Industry and Crafts Sector
مقال
Keywords: local production system; traditional industry; artisans; local development